THE EFFECT OF LEVERAGE, COMPANY AGE, COMPANY SIZE AND SALES GROWTH TOWARDS TAX AVOIDANCE - Sari, Endah Purnama; Gunawan, Yuliana; Carolina, Verani (2021)
This study is targeting to examine and analyze how big does the effect of Leverage, Company Age, Company Size, and Sales Growth have towards Tax Avoidance. Sample used in this study are mining companies listed on the Indonesia Stock Exchange in period of 2016-2018. Researchers are captivated in conducting this study because the mining sector provides a high economic value for the country, but the tax contribution from this particular sector is still minimal. Multiple linear regression is used for data analysis technique, by using the SPSS 20.0 software. This study is anticipated to provide benefits for the government, firms or companies, and for further researchers. The results show that Leverage, Company Age, Company Size, and Sales Growth have a simultaneous effect towards Tax Avoidance.